Implementasi Metode Game Based Learning untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Fiqih - Riska Fatimatus Janah; Amrini Shofiyani (ANWARUL, 2026)
Fiqh learning requires an innovative and student-centered approach so that the learning process becomes more active, engaging, and easier to understand. One approach that can be used is Game-Based Learning, namely electronic or digital game-based learning designed to support the achievement of learning objectives. This study aims to determine the effect of implementing the Game-Based Learning method on increasing students’ interest and learning outcomes in the Fiqh subject at MA Mambaul Ulum Megaluh Jombang. This study used a quantitative approach with a pre-test–post-test design. The research subjects consisted of 37 Grade XI students who participated in Fiqh learning on the topics of marriage and divorce. Data were collected through observation, questionnaires, and tests, and were then analyzed using the Kolmogorov-Smirnov normality test and paired t-test to determine the significant effect. The results showed that the implementation of the Game-Based Learning method had a significant effect on increasing students’ learning interest, with a significance value of 0.01 < 0.05. Students became more active, enthusiastic, and better able to understand the material after participating in game-based learning. The conclusion of this study affirms that the Game-Based Learning method is effective and feasible to use as an innovative learning alternative in increasing students’ learning interest in the Fiqh subject. These findings provide practical implications for Fiqh teachers in designing learning that is more interactive, participatory, and aligned with students’ learning needs.